Examining the bilingual phonological processing and reader profiles for (non)readers of three consistent orthographies: evidence from South Africa - Schaefer, Maxine; Wilsenach, Carien (My University, 2023)
Background: Developmental delays in phonological awareness (PA) and rapid autotomized naming (RAN) contribute to reading difficulties, even in consistent orthographies. In South Africa, evidence suggests that these skills correlate with reading in African languages. However, the extent to which PA and RAN contribute to different reading profiles is not known and little information exists about whether reading profiles are similar across South African languages. Objectives: This longitudinal study examined the phonological processing and reader profiles of isiXhosa, isiZulu and Northern Sotho speaking children at two points in time to determine whether consistent profiles emerged. Method: 59 isiXhosa- and 58 isiZulu-speaking children (analysed as one Nguni group) and 131 Northern-Sotho speaking children were assessed at different points in the foundation phase. Children completed a battery of tests assessing PA, RAN, word reading accuracy, and text reading fluency in their first language and English. Results: Latent profile analysis revealed four profiles found in each group and time point: reader, developing reader, delayed PA and double deficit. These groups differed clearly in terms of PA and RAN. Conclusion: The findings support the universality of PA and RAN for (bilingual) reading and support the need for explicit and systematic phonics instruction for reading development.
Keywords: latent profile analysis; Northern Sotho; phonological awareness; rapid automatized naming; South Africa; word reading; Xhosa; Zulu